1998
DOI: 10.1128/jvi.72.9.7330-7340.1998
|View full text |Cite
|
Sign up to set email alerts
|

Polyomavirus Large T Antigen Binds Cooperatively to Its Multiple Binding Sites in the Viral Origin of DNA Replication

Abstract: Polyomavirus large T antigen binds to multiple 5′-G(A/G)GGC-3′ pentanucleotide sequences in sites 1/2, A, B, and C within and adjacent to the origin of viral DNA replication on the polyomavirus genome. We asked whether the binding of large T antigen to one of these sites could influence binding to other sites. We discovered that binding to origin DNA is substantially stronger at pH 6 to 7 than at pH 7.4 to 7.8, a range often used in DNA binding assays. Large T antigen-DNA complexes formed at pH 6 to 7 were sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…It has previously been shown that the affinity of a DNA-binding protein for DNA increases at low pH. [39][40][41][42] This is also the case with the Tus-TerB and Tus-Ter-lockB complexes and can be explained by an increase in net positive charge of Tus (at low pH), strengthening the electrostatic interactions with the negatively charged phosphate backbone of the DNA. Thus, the difference in stabilization trends observed for Tus-GFP-TerB and Tus-GFP-Ter-lockB at low pH as well as at lower salt conditions is mainly due to the difference in number of nucleotides between these two species.…”
Section: Salt and Ph-dependence Of Free And Dna-bound Tus-gfpmentioning
confidence: 84%
“…It has previously been shown that the affinity of a DNA-binding protein for DNA increases at low pH. [39][40][41][42] This is also the case with the Tus-TerB and Tus-Ter-lockB complexes and can be explained by an increase in net positive charge of Tus (at low pH), strengthening the electrostatic interactions with the negatively charged phosphate backbone of the DNA. Thus, the difference in stabilization trends observed for Tus-GFP-TerB and Tus-GFP-Ter-lockB at low pH as well as at lower salt conditions is mainly due to the difference in number of nucleotides between these two species.…”
Section: Salt and Ph-dependence Of Free And Dna-bound Tus-gfpmentioning
confidence: 84%
“…Then, splicing sites were evaluated in the context of protein sequences that they produce, and exons were identified based on homology to known PyV LTag proteins ( S2 Table ). ORI region was analyzed based on identified and defined SV40 and MCPyV ORI sequences [ 37 39 ].…”
Section: Methodsmentioning
confidence: 99%
“… • T-antigen (a specific DNA-binding protein from simian virus) binds with high affinity to unspecific DNA at pH = 6, with the affinity decreasing substantially at pH = 7.5 ( Wessel et al, 1992 ). • DNA-binding activity of polyomavirus large T-antigen decreases steadily from pH = 6.0 to 8.0 ( Peng and Acheson, 1998 ). …”
Section: Resultsmentioning
confidence: 99%
“…• DNA-binding activity of polyomavirus large T-antigen decreases steadily from pH = 6.0 to 8.0 ( Peng and Acheson, 1998 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation